Conservation agriculture practice and its impact on farmers livelihood status in Bangladesh - Uddin, MT; Dhar, AR (SAARC Journal of Agriculture, 2016)
The study was conducted to assess the impact of conservation agriculture practice on livelihood status of farmers in Bangladesh. A total of 300 farmers (50 focal, 100 proximal and 150 control) from five districts (Mymensingh, Bogra, Tangail, Sherpur and Jamalpur) were selected. Focal farmers were selected purposively; and proximal and control farmers were selected randomly. Descriptive statistics like sum, averages, percentages and ratios were calculated to evaluate the socioeconomic data as well as to identify the nature and extent of conservation agriculture practiced. Expenditure elasticity measured the responsiveness of change in expenditure of the farmers with change in income. Difference-in-difference (DID) analysis and Ravallion test were done to evaluate the impact of conservation agriculture practice on farmers income and expenditure. Multidimensional poverty index (MPI) was used to document the intensity of poverty. About 26.0, 25.0 and 18.6 percent focal, proximal and control farmers, respectively had basic knowledge about conservation agriculture practice; and 28.0, 19.0 and 15.3 percent, respectively received training on such practice. The adoption of different principles of conservation agriculture practice by focal farmers was satisfactory. The BCRs (Benefit cost ratio) for practicing conservation agriculture of focal, proximal and control farmers was 2.15, 2.07 and 1.92, respectively. The results of DID analysis and Ravallion test indicated that the impact of conservation agriculture practice on average annual income and expenditure of the farmers was statistically significant. The expenditure elasticity of focal, proximal and control farmers was 0.31, 0.44 and 0.58 percent, respectively. A remarkable improvement in farmers livelihood status was found after adopting conservation agriculture practice. Input support, motivation, training programmes and extension services by different government and non-government organizations should be properly implemented to raise the awareness and enrich the knowledge of the farmers on conservation agriculture practice. SAARC J. Agri., 14(1): 119-140 (2016)